Preparation and Adsorption Properties of Polymer Particles based on N, N, N', N'-Tetrakis(4-aminophenyl)-1,4-Benzenediamine - Huang, Jian-Yu; Liu, Yong; Huang, Ting-Hong; Liu, Sheng-Zhi; Wu, Ai-Ling (Letters in Organic Chemistry, 2024)
Two polymer particles have been prepared by the reaction of N, N, N', N'-tetrakis(4- aminophenyl)-1,4-benzenediamine, 4, 4-biphenyldialdehyde and isophthalaldehyde, and characterized by SEM, FTIR and XRD. Based on methylene blue as the model pollutant, the adsorption properties of two polymer particles have been observed by using different adsorbent dosages, adsorption times and adsorption temperatures. Experimental data show that the removal rates of methylene blue wastewater are 74 % for polymer A and 68 % for polymer B, and the removal rates are up to 84% for polymer A and 74 % for polymer B after photo-catalytic treatment. All these suggest that the adsorption performance of polymer A is more excellent than that of polymer B. In addition, the methylene blue adsorption of the two Schiff base products conforms to the Freundlich adsorption isothermal model.
Keywords: Polymer particles